Husband's Participation in Method Selection Contraception in Fertilizing Couples at the Gulbung Village Support Health Center Pangarengan District Sampang District - Siti Mukarromah; Andari Wuri Astuti; Yuli Isnaeni (Universitas STRADA Indonesia, 2025)
Family planning (FP) coverage in Pangarengan District declined from 84% to 74%, partly due to cultural beliefs that contraception is solely a woman’s responsibility. This study explores the role of husbands in contraceptive selection among couples at the Gulbung Village Sub-Health Center using a qualitative phenomenological approach. Ten husbands of FP acceptors were interviewed using purposive sampling. Thematic analysis revealed that husbands’ roles were influenced by their initial knowledge, information sources (midwives, social media, environment), and cultural norms. Their support included financial aid, accompanying wives to FP services, and decision-making discussions. Barriers included limited knowledge, rigid gender roles, and sociocultural pressures. Health workers acted as communicators, facilitators, and counselors, but often did not involve husbands actively in counseling. Husbands’ expectations centered on supporting their partners and ensuring family welfare. Overall, the study highlights the need to improve husband involvement in FP through inclusive health education and culturally sensitive counseling approaches.